Participatory Didactics and the role of feedback through game-based technologies - Maria Iavarone; Francesco Lo Presti; Orazio Stangherlin (Firenze University Press, 2017)
The aim of this paper is to emphasize the importance of feedback in the knowledge and learning processes and the central role that it can play through smart-device technologies.The contribution is aimed at analyzing some issues arising from theoretical backgrounds and guidelines for innovative instructional design to enhance the experience in digital interaction. The research conducted at the University Parthenope of Naples, with a group of 149 students enrolled in different courses of study, used game-based technologies and a platform called Kahoot which offered the possibility to create a single response quiz-game. In light of the theoretical framework analyzed, the experience and the results, it is reasonable to argue that game-based technologies enable a more effective engagement, improving overall learning processes and optimizing knowledge retention.   Didattiche partecipative e ruolo del feedback attraverso tecnologie game-based Lo scopo di questo articolo è sottolineare l'importanza del feedback nei processi di conoscenza e di apprendimento ed il ruolo centrale che esso può svolgere tramite l'ausilio di tecnologie smart-device. Il contributo tratteggia gli orientamenti prevalenti per una progettazione didattica che preveda l'utilizzo di tecnologie digitali. A tale proposito l'analisi si è avvantaggiata di evidenze empiriche acquisite nell'ambito di un'esperienza svolta presso l'Università Parthenope di Napoli, con la partecipazione di 149 studenti di diversi corsi di studio, che ha previsto l'uso di tecnologie game-based per la realizzazione di un quiz-game tramite la piattaforma Kahoot. Alla luce del quadro teorico, dell'esperienza e dei risultati, è ragionevole ritenere che le tecnologie game-based contribuiscano a migliorare complessivamente i processi di apprendimento consentendo un più efficace engagement ottimizzando l'acquisizione delle conoscenze.